Comparison of an HCG-only trigger versus dual trigger for final oocyte maturation in a progestin-primed ovarian stimulation protocol. Issue 6 (December 2022) - Li, Qian; Li, Xiaolan; Li, Tingting; Xu, Linan; Wang, Yanfang; Huang, Rui
Abstract: Research question: Is there any difference in clinical outcomes between a human chorionic gonadotrophin (HCG)-only trigger and a dual trigger combining gonadotrophin-releasing hormone agonist (GnRHa) and HCG in a progestin-primed ovarian stimulation (PPOS) protocol? Design: This retrospective cohort study included women younger than 40 years old with a normal ovarian reserve who underwent IVF/intracytoplasmic sperm injection treatment with a PPOS protocol. Participants were allocated to two groups according to the triggering medicines. The clinical outcomes were compared, with cumulative live birth rate (CLBR) being the primary outcome. Results: In total, 1066 women were included, 565 in the HCG-only group and 501 in the dual trigger group. Demographic parameters were comparable between the groups. Fewer oocytes were retrieved in the HCG-only trigger group (dual trigger 12.56 ± 7.12 versus HCG-only trigger 11.62 ± 6.02, P = 0.020). No significant difference was observed in the numbers of two-pronuclear embryos (7.12 ± 4.90 versus 6.76 ± 4.45, P = 0.208) and high-quality embryos (4.01 ± 3.70 versus 3.96 ± 3.32, P = 0.815). The CLBR after one complete cycle was also similar (40.72% versus 43.72%, P = 0.354). Multivariate logistic analysis confirmed that the trigger method had no association with CLBR (odds ratio [OR] 0.763, 95% confidence interval [CI] 0.578–1.005, P = 0.055) in the PPOS-treated patients. Conclusions: Compared with the HCG-only trigger group, comparable embryological and clinical outcomes were achieved, although more oocytes were retrieved in the dual trigger group. This suggests that there may be no extra benefit from dual triggering, and that it should not be recommended for routine use in the general population undergoing PPOS protocols.